Pengaruh Corporate Governance Terhadap Manajemen Laba Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Audrey Annabella, Liana Susanto (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this research is to obtain empirical evidence of board independence, board size, board meeting and institutional ownership on earnings management with firm size as moderating variable of manufacturing companies listed in the Indonesian Stock Exchange from 2017-2019. This research used purposive sampling method for a total of 76 companies’ data in 3 years. This research used E-Views 10 and Microsoft Excel 2019 for data processing. The results of this research showed that board independence, board meeting and institutional ownership negatively affect earning management whilst board size does not affect earnings management. Firm size as moderating variable has a positive effect of board independence and institutional ownership on earnings management.